Food, Fermentation and Micro-organisms. - Bamforth, Charles W., 1952- (John Wiley & Sons, 2007)
Fermentation and the use of micro-organisms is one of the most important aspects of food processing, an industry worth billions of US dollars world-wide. From beer and wine to yoghurt and bread, it is the common denominator between many of our foodstuffs. In his engaging style Professor Charles Bamforth covers all known food applications of fermentation. Beginning with the science underpinning food fermentations, Professor Bamforth looks at the relevant aspects of microbiology and microbial physiology, moving on to cover individual food products, how they are made, what is the role of fermenta.